General results of complete convergence and complete moment convergence for weighted sums of some class of random variables. Issue 15 (2nd August 2016) - Wang, Xuejun; Hu, Shuhe; Volodin, Andrei
ABSTRACT: In the article, the complete convergence and complete moment convergence for weighted sums of sequences of random variables satisfying a maximal Rosenthal type inequality are studied. As an application, the Marcinkiewicz–Zygmund type strong law of large numbers is obtained. Our partial results generalize and improve the corresponding ones of Shen (2013 ).